Perancangan Aplikasi Rekomendasi Jenis Kandidat Web Programmer Menggunakan Metode Weighted Aggregated Sum Product Assesment - Herman; Didik; Andy (Bulletin of Computer Science Research, 2024)
Thanks to the development of technology in this digital era, web-based software has become popular and widely used in various fields of life. In order to design a good quality web, a reliable web developer is needed to perform tasks according to their respective expertise. Web developers themselves are divided into three types, namely front-end, back-end, and full-stack developers. The problem encountered is the difficulty of recommending the type of web developer candidate by manually calculating and analyzing the candidate's ability. Inaccuracy in the calculation process will affect the results of the assessment in the recommendation. Therefore, this research aims to build an application that can solve the problem of calculating and assessing the type of web developer candidate using the Weighted Aggregated Sum Product Assessment (WASPAS) method. The WASPAS method was chosen because of its ability to combine various assessment criteria and provide more accurate and objective results. The designed application is expected to assist companies in identifying candidates that best suit their needs, reduce errors in the selection process, and increase the efficiency and effectiveness of recruitment. Thus, companies can more easily find the right and high-quality web developers, according to the expertise needed for their projects.